Chapter Introduction The Country-of-Origin (COO), Country-of-Origin (COO) Dimensions, and Country-of-Origin Effect (COE) - General Overview and Theoretical Approaches - Witek-Hajduk, Marzanna K. (Taylor & Francis, 2024)
This introductory chapter provides a general overview of the content of this monograph contains and its key areas of focus, namely a multi-faceted approach to country-of-origin (COO) and its dimensions, and country-of-origin effect (COE), including both consumer and strategic perspectives, as well as both developed countries and emerging/developing markets. Thus, it presents a general overview of the streams of research on the national origin of the companies/products/brands, as well as on the concept of COO and its dimensions, COI, COE, and related terms and concepts, such as "liability-of-origin", the "made-in" label, geographical indications (GIs), etc. Moreover, various perspectives that can be adopted when considering these occurrences are discussed too. Finally, it states the novelty of the monograph, i.e. its interdisciplinary approach to the field, covering various aspects of COO, its implications for international business, further theoretical developments regarding COO, and empirical evidence delivered by scholars representing different fields of science.